Effectiveness of psychoeducation of postpartum depression (a study in health services in subprovince Nias, North Sumatra) - Nazara, Yafeti (Indonesian Journal of Obstetrics and Gynecology, 2009)
Objective: To evaluate the effectiveness of psycho-education intervention which is given to postpartum mothers in preventing the existence of postpartum depression and its relation to age, parity, occupation, education and family support. Methods: This research used a quasi experimental with post test only design. Research was implemented at public hospital of Gunung Sitoli and five community health centres in Sub-Province of Nias taken by random on since May - July 2006. There were 85 mothers with normal childbirth as samples. They were accompanied by their husband, condition of mothers and their babies were healthy without any complication. This research used an Edinburg Pascasalin Depression Scale questionnaire as instrument and psycho- education intervention was given with a booklet as media. Results: 85 subjects were included, 40 were intervention group and 45 control group. This research showed that psycho-education intervention was effective significantly (p= 0,001), Odds Ratio (OR): 5,924 (95 % CI : 2,081-16,868) to prevent the postpartum depression occurrence. The most dominant variable in effectiveness of psycho-education intervention is family support variable with pvalue is p = 0,001, OR : 80 (95 % CI : 6,069-1054,570). Conclusion: Psycho-education intervention is very effective for preventing the postpartum depression occurrence after controlled by family support factor. [Indones J Obstet Gynecol 2009;33-4:216-23] Keyword: psycho-education, postpartum depression, family support.